2015
DOI: 10.1152/jn.00058.2015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the functional link between area MT LFPs and motion detection

Abstract: -The evolution of a visually guided perceptual decision results from multiple neural processes, and recent work suggests that signals with different neural origins are reflected in separate frequency bands of the cortical local field potential (LFP). Spike activity and LFPs in the middle temporal area (MT) have a functional link with the perception of motion stimuli (referred to as neural-behavioral correlation). To cast light on the different neural origins that underlie this functional link, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…How neural activities control the behavior (either choice or performance) is a crucial question in neuroscience. Previous studies have reported a link between behavioral performance and the neural activity in different brain areas, such as the trigeminothalamic system (Maixner et al, 1989 ; Bushnell et al, 1993 ), the somatosensory system (Sinclair and Burton, 1991 ; Romo et al, 1996 ), superior colliculus (Horwitz and Newsome, 2001 ) and visual cortex (Newsome et al, 1989 ; Britten et al, 1996 ; Shadlen et al, 1996 ; Horwitz and Newsome, 2001 ; Cook and Maunsell, 2002 ; Barberini et al, 2005 ; Liu and Newsome, 2005 , 2006 ; Cohen and Newsome, 2009 ; Cohen and Maunsell, 2010 ; Kajikawa and Schroeder, 2011 ; van Ede et al, 2012 ; Smith et al, 2015 ). Additionally, it has been reported that behavioral choice is closely connected to the neural activity (Johansson and Vallbo, 1979 ; Newsome et al, 1989 ; Bushnell et al, 1993 ; Britten et al, 1996 ; Romo et al, 1996 ; Shadlen et al, 1996 ; Horwitz and Newsome, 2001 ; Cook and Maunsell, 2002 ; Barberini et al, 2005 ; Liu and Newsome, 2005 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…How neural activities control the behavior (either choice or performance) is a crucial question in neuroscience. Previous studies have reported a link between behavioral performance and the neural activity in different brain areas, such as the trigeminothalamic system (Maixner et al, 1989 ; Bushnell et al, 1993 ), the somatosensory system (Sinclair and Burton, 1991 ; Romo et al, 1996 ), superior colliculus (Horwitz and Newsome, 2001 ) and visual cortex (Newsome et al, 1989 ; Britten et al, 1996 ; Shadlen et al, 1996 ; Horwitz and Newsome, 2001 ; Cook and Maunsell, 2002 ; Barberini et al, 2005 ; Liu and Newsome, 2005 , 2006 ; Cohen and Newsome, 2009 ; Cohen and Maunsell, 2010 ; Kajikawa and Schroeder, 2011 ; van Ede et al, 2012 ; Smith et al, 2015 ). Additionally, it has been reported that behavioral choice is closely connected to the neural activity (Johansson and Vallbo, 1979 ; Newsome et al, 1989 ; Bushnell et al, 1993 ; Britten et al, 1996 ; Romo et al, 1996 ; Shadlen et al, 1996 ; Horwitz and Newsome, 2001 ; Cook and Maunsell, 2002 ; Barberini et al, 2005 ; Liu and Newsome, 2005 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complex neural tasks such as converting sensory information into appropriate motor actions and the associated decision processes require carefully and dynamically coordinated neural activity in networks of cortical areas (15). Many studies have shown that the response variability of the contributing populations of sensory neurons play a central role in determining the variations of behavioral response (618), as well as perceptual decisions (1921). Local field potentials (LFPs)—signals representing the extracellular neural activity in a local volume of brain tissue—provide a measure for activities mediated by relatively localized neuronal pools (22, 23).…”
mentioning
confidence: 99%
“…These signals, extracted from the low-frequency (<500 Hz) components of extracellular neural signals, reflect mainly the collective synaptic activities across local neural populations (23, 24), predominantly induced by the local spiking activity (25). Recent research has shown that LFP signals could provide useful information on how neural activities are linked to behavior (12, 14, 16, 17, 26). These studies have demonstrated that the power of gamma and high-gamma (50 to 200 Hz) LFPs, as well as multiunit neural activities, in area MT of primate visual cortex are linked to behavioral outputs in a trial-by-trial manner (14, 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary investigations into visual areas have shown that oscillatory components of local field potential (LFP) (Liu and Newsome, 2006;Womelsdorf et al, 2006;Smith et al, 2015;Khamechian et al, 2019) and neural spiking activity (Liu and Newsome, 2005;Smith et al, 2015;Parto Dezfouli et al, 2018) could provide useful information about how neural activities are linked to visuomotor behavior. These studies have reported a trial-by-trial correlation between the power of beta (10-30 Hz) (Smith et al, 2015), gamma, and high-gamma (50-200 Hz) (Liu and Newsome, 2006) LFPs and behavioral output. Moreover, they have shown that the strength of gamma (Womelsdorf et al, 2006) and high-gamma synchronization (Khamechian et al, 2019) between sensory neurons in the dorsal and ventral visual pathway, respectively, predict the speed of behavioral responses.…”
Section: Introductionmentioning
confidence: 99%